2013
DOI: 10.1002/bio.2508
|View full text |Cite
|
Sign up to set email alerts
|

Transfection efficiency of normal and cancer cell lines and monitoring of promoter activity by single‐cell bioluminescence imaging

Abstract: The bioluminescence system (luciferase reporter assay system) is widely used to study gene expression, signal transduction and other cellular activities. Although transfection of reporter plasmid DNA to mammalian cell lines is an indispensable experimental step, the transfection efficiency of DNA varies among cell lines, and several cell lines are not suitable for this type of assay because of the low transfection efficiency. In this study, we confirm the transfection efficiency of reporter DNA to several canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…Kojic acid and rutin were purchased from WAKO (Osaka, Japan). The human glioblastoma U251 cell line was obtained as reported previously . U251 cells stably transfected with pBipPro‐Luc (U251/Luc), in which the promoter region of Bip was cloned into the pGL4.14 vector (Promega, Madison, WI, USA), were established previously .…”
Section: Methodsmentioning
confidence: 99%
“…Kojic acid and rutin were purchased from WAKO (Osaka, Japan). The human glioblastoma U251 cell line was obtained as reported previously . U251 cells stably transfected with pBipPro‐Luc (U251/Luc), in which the promoter region of Bip was cloned into the pGL4.14 vector (Promega, Madison, WI, USA), were established previously .…”
Section: Methodsmentioning
confidence: 99%
“…Since our previous study showed that bioluminescence imaging at the single-cell level with the LV200 imaging system is a powerful tool for analyzing gene expression (based on a reporter assay specific to cells with low transfection efficiency) [23], we applied this imaging technique to evaluate the effect of each treatment on Hsp70 expression. Although the transfection efficiency of reporter plasmid DNA in BT20 was not so high compared with that of other cancer cells with high transfection efficiency, such as HeLa cells [23], analyzing Hsp70 promoter activation on single-cell imaging proved to be effective for time-course monitoring of this promoter in living cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the transfection efficiency of reporter plasmid DNA in BT20 was not so high compared with that of other cancer cells with high transfection efficiency, such as HeLa cells [23], analyzing Hsp70 promoter activation on single-cell imaging proved to be effective for time-course monitoring of this promoter in living cancer cells. Treatment with Antp-TPR with or without R11-Hsp70 did not activate the Hsp70 promoter in breast cancer cells, whereas treatment with 17-AAG did (Figure 4C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP dynamics in cancer cells were measured after treatment with the hybrid peptide by single‐cell bioluminescence imaging using the LV200 system (Olympus) as described previously (Akiyoshi & Suzuki, ; Horibe et al., ; Kikuchi et al., ). Briefly, U251 cells stably transfected with firefly luciferase‐containing reporter plasmids of the cytomegalovirus (CMV) promoter pGL4.50 (U251/CMVLuc; Promega) were prepared after the transient transfection with Lipofectamine LTX in selective medium containing 200 μg/ml hygromycin B (Nacalai Tesque), and bioluminescence images were obtained with the LV200 system.…”
Section: Methodsmentioning
confidence: 99%